The Relationship between Fatherless and Marriage Anxiety in Early Adult Women in Surabaya - Shifani, Andrea; Fitriana, Qurrota A’yuni (Character Jurnal Penelitian Psikologi, 2026)
The decline in the number of marriages in Surabaya, which reached 14,194 events in 2025, reflects a change in the perspective of young adults toward commitment, partly triggered by the fatherless phenomenon due to divorce. This study aims to determine the relationship between being fatherless and marriage anxiety in early adult women in Surabaya. This study uses a correlational quantitative approach with purposive sampling techniques involving 156 early adult women (18-40 years old) who experienced fatherlessness due to parental divorce. The research instrument used the fatherless scale based on aspects from Lamb, Pleck, Levine, and Charnov, and the marriage anxiety scale based on aspects from Obeid et al. Data analysis was conducted using Pearson Product Moment correlation through JASP software. The research results showed a correlation coefficient value of r = 0.573 with a significance of p < 0.001, indicating a positive relationship between fatherlessness and marriage anxiety. The higher the level of fatherlessness, the greater the tendency for marriage anxiety experienced. This condition manifests in the emergence of negative perceptions toward relationships, fear of commitment, and a tendency to prioritize personal life as a form of self-defense. Abstrak Penurunan angka pernikahan di Surabaya yang mencapai 14.194 peristiwa pada tahun 2025 mencerminkan adanya perubahan cara pandang dewasa awal terhadap komitmen, yang salah satunya dipicu oleh fenomena fatherless akibat perceraian. Penelitian ini bertujuan untuk mengetahui hubungan antara fatherless dengan kecemasan pernikahan pada wanita dewasa awal di Surabaya. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan teknik purposive sampling yang melibatkan 156 wanita dewasa awal (18-40 tahun) yang mengalami fatherless akibat perceraian orang tua. Instrumen penelitian menggunakan skala fatherless berdasarkan aspek dari Lamb, Pleck, Levine, dan Charnov dan skala kecemasan pernikahan berdasarkan aspek dari Obeid dkk. Analisis data dilakukan menggunakan korelasi Pearson Product Moment melalui software JASP. Hasil penelitian menunjukkan nilai koefisien korelasi sebesar r = 0,573 dengan signifikansi p < 0,001, artinya terdapat hubungan positif antara fatherless dan kecemasan pernikahan. Semakin tinggi tingkat fatherless, semakin meningkat pula kecenderungan kecemasan pernikahan yang dialami. Kondisi ini terwujud dalam munculnya persepsi negatif terhadap relasi, ketakutan akan komitmen, hingga kecenderunagn memprioritaskan kehidupan pribadi sebagai bentuk pertahanan diri.